Starring Dante - Ascoli, Albert Russell (Religions, 2019)
This essay offers an example of a guiding thread in my own research on and teaching of Dante's Commedia. Specifically, I will follow a strand that leads us from Dante's encounter with the "bella scola" of classical poets in Inferno Canto 4, through a key scene in the Purgatorio where Dante and his guide Virgil meet the late classical poet Statius, to the remarkable six-canto suite in the Heaven of the Stars, sign of Gemini, in which Dante-poet has Dante-character undergo a series doctrinal tests on the theological virtues. His successful response to the challenges posed by the apostles Peter, James, and Paul doubly authorizes him as poet and as Christian teacher of the highest order. These unique experiences as Dante is successively introduced to and made part of a rising series of elite groups, highlights his double role as humble student and prospective teacher of others. Among the various aims of this essay is to give a sample of a way in which teachers of the Commedia may address the perennial pedagogical problem of how to account for the extraordinary spectacle of a first-person epic that at once expresses deep piety with profound "charitas" (spiritual love) and appears as the absolute height of a self-aggrandizement seemingly inconsistent with Christian humility. Another is to suggest one possible strategy for teaching the Comedy as a whole, and especially the final canticle, the Paradiso, which even Dante himself notoriously thinks is "not for everyone".